Evaluation of Tourism Policies in Relation to Ecotourism in Jaffna, Sri Lanka - Vipulan, Piratheepa; Chan, Ngai Weng; Ghazali, Suriati (European Publisher, 2019)
Jaffna District is situated in the northern part of Sri Lanka and the tourism sector is being promoted in post war development. Jaffna has opportunities and potentials for ecotourism development. Presently, national, provincial and district level plans have been prepared to promote tourism in Jaffna District. However, there are lacks of initiatives related with ecotourism development in this region. This study focuses on the evaluation of the extent to which these tourism plans encourage ecotourism development in the Jaffna district. Primary and secondary data have been used in this study. The main method is content analysis of these plans. Results of the analysis showed that the initiatives on ecotourism have not been promoted based on true ecotourism concepts in all three documents. While comparing the three policy documents, which give certain focus on ecotourism development. But it does not adequately define ecotourism zones, resources, regulations and responsibilities. At this juncture, well prepared ecotourism policy is very vital to Jaffna district for the conservation and enhancement of the environmental attributes, local people wellbeing as well as regional development. This study recommends that it is high time to study the ecotourism potentials of Jaffna District in detail, put in place regulations to encourage ecotourism, conserve the environment and ecotourism attractions, provide intensive training to stakeholders, and increase the awareness and involvement of local communities in the development of ecotourism in the study area.